Age is not just a number: age awareness, subjective nearness-to-death, self-esteem, and depressive symptoms among older adults. (2nd June 2020) - Bergman, Yoav S.; Bodner, Ehud
Abstract: Objectives : Humans often hold structured generalizations about themselves, which include attributes of qualities or characteristics they consider as important to their personal self-definitions. In this regard, holding one's age as an important defining personal category (high age awareness) was demonstrated to be connected with increased distress in older adults. However, little is known about the manner by which this connection is affected by individuals' perceptions regarding how close they are to their death on the one hand, and their personal resources on the other hand. Accordingly, the current research examined whether the connection between age awareness and depressive symptoms is mediated by subjective nearness-to-death, and whether this mediation is moderated by self-esteem. Method : A convenience sample of 386 older adults was collected using an online panel survey (age range 60-97, M  = 71.62, SD  = 6.88). Participants were requested to fill out scales assessing age awareness, subjective nearness-to-death, self-esteem, and depressive symptoms, as well as various sociodemographic scales. Results : Age awareness was associated with increased subjective nearness-to-death and depressive symptoms. In line with the hypotheses, subjective nearness-to-death mediated the age awareness-depressive symptoms connection, and this mediation was moderated by self-esteem. Conclusion : Age awareness is an important concept in old age, and is connected with increased depressive symptoms. We discuss this issue in line with Terror Management Theory, and emphasize the relevance of personal resources, such as feeling far from death and holding a positive view of oneself, in this regard.